Industry - Elliott, Deborah (Wayland Hove, 1994)
"Industry" by Deborah Elliott, published in 1994, is part of the "Into Europe" series. This 48-page book examines various industries across Europe, discussing their development, impact, and significance within the European context. It is illustrated throughout in color.